Operating Systems : International Edition. - Stallings, William (2013)
For introductory courses on operating systems.Operating Systems: Internals and Design Principles provides a comprehensive and unified introduction to operating systems topics. Stallings emphasizes both design issues and fundamental principles in contemporary systems and gives readers a solid understanding of the key structures and mechanisms of operating systems. He discusses design trade-offs and the practical decisions affecting design, performance and security. The book illustrates and reinforces design concepts and ties them to real-world design choices through the use of case studies in UNIX and Windows.Operating Systems: Internals and Design Principles, 6e received the 2009 Textbook Excellence Award from the Text and Academic Authors Association (TAA)!.
Discussion Topics -- BACI -- Glossary -- References -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books